A knowledge-based view of the extending enterprise for enhancing a collaborative innovation advantage. (1st January 2014) - Alguezaui, Salma; Filieri, Raffaele
The extended enterprise (EE) framework emerged in high-tech industries with large chains of suppliers to address the current challenges related to innovation and competition in complex scenarios. Since its conceptualisation, many transformations have interested the business landscape, such as the emergence of the knowledge economy, the rise of a more open approach to innovation, and the outsourcing and offshoring of value creating activities. This paper acknowledges these transformations and attempts to provide an updated model of the EE, termed extending enterprise, based on the knowledge-based view of the firm. The paper is conceptual in nature and research heralding from supply-chain management, operations, strategy, innovation, knowledge management has been brought together in this paper. After more than ten years from its conceptualisation, this is the first attempt that discusses the EE framework in light of the knowledge economy.